Strategi Telkomsel dalam Transformasi menjadi Perusahaan Digital - Syarif, Usman; Aminda, Renea Shinta (Jurnal Manajemen, 2019)
The transformation to digital companies must be carried out by Telkomsel according to Gerhard Berhold, 2019 there are 5 basic things why companies must transform to digital; Increased customer demand, higher procurement competencies, growing competition, fast pace, new technology. Digital technology that has not been well anticipated causes the company’s revenue to decline. This research will see whether the transformation carried out by Telkomsel is going well. Using John Kotter’s theory in his book 8 Steps Process for Leading Change. The results obtained are all the steps that have been done well by Telkomsel, except for one step which is to formulate and socialize the vision of transformation.